KEBERHASILAN KONSELING DITINJAU DARI TAHAP PEMBINAAN HUBUNGAN DAN TATA RUANG BK - Trisuko Nugroho, Felix (Widya Warta, 2020)
This  study  aims  to  analyze  the development  phase  and  spatial  relationship  of  guidance  and counseling  influence  on  the  success  of  counseling.  The  population  in  this  study  were  all students  of  SMPN  2  Kabupaten  Sleman  in  2016/2017  academic  year  consisting  of  93 students.  The  sampling  technique  used  by  the  author  was  saturation  sampling.  The  data, which  were  obtained  by  using  scales  of  questionnaires,  were  counseling  relationship  scale, spatial  scale,  and  counseling  scale.  The  data  were  analyzed  using  multiple  linear  regression techniques.  The  model  of  regression  equation  was  Y=11  940+0326+1266.  Further  analysis results showed that:           1) the success of counseling led to counseling relationship phase, proven  t  hit=3782  (p>0,05),    2)  spatial  guidance  and  counseling  influenced  the  success  of counseling,  proven  t  hit=8076  (p>0,05),  3)  development  phase  and  spatial  relationships  of guidance and counseling influenced the success of counseling, proven t hit=76830(p> 0,05)